The Dynamics Of Improving Education Quality Indicators Through The Integration Of Artificial Intelligence Technologies (Open Academia: Journal of Scholarly Research, 2026)
This study analyzes the dynamics of education quality indicators following the implementation of artificial intelligence technologies in Uzbekistan. The impact of adaptive learning systems, automated assessment, learning analytics, and digital platforms on students’ academic achievement, motivation, independent thinking, and digital competence was examined using statistical methods. The findings demonstrate that AI-based educational tools enhance learning effectiveness, support individualized instruction, and ensure a stable improvement in educational outcomes